A concurrent episode of two neoplasms in a toddler-age child - Muaz A Alrazzak (Thieme Medical and Scientific Publishers Pvt. Ltd., 2014)
Childhood neoplasms are relatively rare and represent only about 1- 2% of the total incidence of neoplasms in United States. Concurrent episode of childhood cancer is uncommon and usually related to a cancer genetic syndrome. Li Fraumeni Syndrome refers to an autosomal dominant condition that is manifested by the development of certain cancers in early childhood and an increased lifetime risk for developing multiple primary cancers including sarcoma, breast cancer, leukemia, bone cancer, and others. We report a case of a 21-month-old girl who was found to have orbital embryonal rhabdomyosarcoma and adrenocortical tumor concurrently.